Harrod versus Thirlwall: A Reassessment of Export-Led Growth - Jamee K. Moudud (Levy Economics Institute of Bard College, 2000)
This paper contrasts the different approaches to export-led growth used by Harrod and Thirlwall. It argues that, unlike Thirlwall's model, Harrod emphasized the importance of both demand- and supply-sides in his analysis of growth. The fundamental difference between the two authors lies in their differing characterizations of the long run. While both authors assume unemployment, Thirlwall's long run is presumably consistent with excess capacity, while Harrod's warranted path assumes normal capacity growth. Harrod's perspective suggests that if the warranted growth rate exceeds the natural growth rate, desired saving is excessive relative to the amount that is necessary to maintain the economy along its maximum growth path. Under these circumstances, rising exports have the beneficial effect of adjusting the warranted path to the economy's maximum growth path while, at the same time, giving a boost to the actual growth rate. If, however, the warranted growth rate is lower than the natural rate, then rising net exports have to be accompanied by appropriate fiscal and/or tax policies to raise warranted growth. In either case, the long-run growth rate is regulated by the social saving rate (other things equal). Data for a number of OECD countries tend to confirm this implication of what might be called a classical-Harrodian perspective. The Harrodian growth tradition suggests that growth in an open economy, with normal capacity utilization and persistent cycles, can be characterized as export-oriented rather than export-led since both demand- and supply-side factors are important.
Keywords: 330